Manufacturing strategies and tribology of tailored tool surface topographies for enhanced lubrication in metal forming - Sulaiman, Mohd Hafis; R.N, Farahana; Mohd Jamir, Mohd Ridzuan; Mohammad Jaafar, Muhammad Hasnulhadi (Tribology & Metal Forming Research Group, 2019)
Lubricants are applied extensively in metal forming. Currently, methods to prevent wear are always emphasize the need for lubricants with ability to form boundary layers, chemically bonded to tool and workpiece surfaces. Tailored tool surface topography, as a kind of new engineered tool surfaces consisting of lubricant pockets on a hard tool material, has attracted great attention from investigators in facilitating micro-hydrodynamic lubrication impeding wear on tool surface by less harmful lubricants in metal forming. In the present paper, overview of manufacturing strategies of tailored surface topographies on hard tool material reported by different investigators are explained. Recent development and challenges on adopting strategic tool surface topography as one of environmental friendly alternatives for enhanced lubrication in metal forming and their suggested amount of real contact area α influencing friction are discussed.